1999
DOI: 10.1212/wnl.53.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing is involved in cluster headache but not in chronic paroxysmal hemicrania

Abstract: Our data suggest that central structures generating ERPs are involved in the pathophysiology of cluster headache during the cluster period but not outside the cluster period. This is in concordance with recent neuroimaging findings on the central role of the hypothalamus and the right frontal cortex in cluster headache and supports the hypothesis of a central origin of cluster headache. Furthermore, the data suggest that cluster headache and chronic paroxysmal hemicrania are distinct entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 36 publications
1
45
0
2
Order By: Relevance
“…Limited electrophysiological studies using event-related potentials (ERPs) have been done in cluster headache patients to try and understand some of the reported higher brain abnormalities. For example, Evers et al [9] found a latency increase of P300 in cluster headache patients during the cluster period in a visual ERP test. As P300 latency is an indicator of cognitive performance [10], the authors concluded that cognitive processing is impaired during the cluster period reinforcing the possibility that cluster headache has a central origin.…”
Section: Introductionmentioning
confidence: 99%
“…Limited electrophysiological studies using event-related potentials (ERPs) have been done in cluster headache patients to try and understand some of the reported higher brain abnormalities. For example, Evers et al [9] found a latency increase of P300 in cluster headache patients during the cluster period in a visual ERP test. As P300 latency is an indicator of cognitive performance [10], the authors concluded that cognitive processing is impaired during the cluster period reinforcing the possibility that cluster headache has a central origin.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that an involvement of the visual cognitive processing may be impaired in patients with CH [9]. These data were confi rmed by a second study comparing cognitive processing via visually evoked ERPs in CH patients with patients suffering from hemicrania continua [10].…”
Section: Visually Evoked Event-related Potentialsmentioning
confidence: 81%
“…Presumably, it is the unrelieved pain of CH that predisposes the sufferer to aggressive or suicidal behavior, but it also is possible that impaired cognitive processing, which is shown to be present throughout the cluster period, not just during individual headache attacks, also plays a role [27]. In any event, the consequences of such behavior may be blamed on the physician, particularly if diagnosis has been delayed or inappropriate treatment has been rendered.…”
Section: Results [Reference] Source Legal Issuementioning
confidence: 99%